CURVE FITTING METHOD FOR ESTIMATING OUTER RACE WAVINESS OF A CYLINDRICAL BEARING SUBJECTED TO STATIC LOAD - MAGIANO FAIZUL AGUS (NIM : 23109031); Pembimbing : Prof. Dr. Ir. Komang Bagiasna, KEMAL
Imperfections on bearing manufacturing process can cause wavy surface on bearing races (waviness). This wavy surface can be viewed as a deformation that occured on bearing races. Based on Hertzian contact stress concept, bearing races deformation subjected to surface contact can cause excitation force. Therefore, this excitation force will generate vibration when the bearing in operation. This research will examine the vibration characteristics of bearing due to waviness on bearing races. Based on these characteristics, this research will be develop a method to estimate the form of the wavy surface on bearing races. Roll passage frequency (RPF) and its sideband will be also identified on this research. The experimental part of this research consists of FRF (Frequency Response Function) and linear spectrum measurement. These measurements are conducted to obtain force spectrum occured on the bearing. FRF and linear spectrum measurement are done at various rotational speed and static load. Rotational speed are being varied by 300 rpm, 450 rpm, 600 rpm and 750 rpm while the static load are varied by 200N, 400N and 600N in horizontal direction. This research has developed a curve fitting method to estimate waviness on bearing outer race. Waviness on outer race bearing were found to have an amplitude of 0.196 μm with the order of 8. In addition, it is also found that static load given to the bearing will yields RPF signal and its sidebands.